2010
DOI: 10.1155/2010/612948
|View full text |Cite
|
Sign up to set email alerts
|

S-Layer Glycoproteins and Flagellins: Reporters of Archaeal Posttranslational Modifications

Abstract: Many archaeal proteins undergo posttranslational modifications. S-layer proteins and flagellins have been used successfully to study a variety of these modifications, including N-linked glycosylation, signal peptide removal and lipid modification. Use of these well-characterized reporter proteins in the genetically tractable model organisms, Haloferax volcanii, Methanococcus voltae and Methanococcus maripaludis, has allowed dissection of the pathways and characterization of many of the enzymes responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 139 publications
0
49
0
Order By: Relevance
“…Our current understanding of N-glycosylation in the methanogens has come from a significant body of work addressing the structure and genetics of this PTM in two species of Methanococcus, namely, M. voltae and M. maripaludis (104)(105)(106)(107). In addition, in vitro biochemical work using purified enzymes has further con-tributed to our understanding of the process in this group of Archaea (108)(109)(110).…”
Section: Pathway Of N-linked Glycosylation In Methanogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current understanding of N-glycosylation in the methanogens has come from a significant body of work addressing the structure and genetics of this PTM in two species of Methanococcus, namely, M. voltae and M. maripaludis (104)(105)(106)(107). In addition, in vitro biochemical work using purified enzymes has further con-tributed to our understanding of the process in this group of Archaea (108)(109)(110).…”
Section: Pathway Of N-linked Glycosylation In Methanogensmentioning
confidence: 99%
“…volcanii and S. acidocaldarius, the S-layer glycoprotein has been used extensively as the model reporter of N-glycosylation (6,107,118,222). This protein is particularly important in Archaea, as opposed to Bacteria, since most Archaea, including these two organisms (63,223), have a cell envelope consisting solely of an S-layer overlying a cytoplasmic membrane without the benefit of an intermediate peptidoglycan equivalent, a situation never found in S-layer-bearing Bacteria (224,225).…”
Section: Biological Effects Of N-linked Glycosylation Perturbations Imentioning
confidence: 99%
“…A deletion mutant analysis of three glycosyltransferases and an oligosaccharyltransferase (Stt3p homologue) from M. maripaludis revealed that these genes were responsible for flagellin glycosylation supported by the fact that glycan reduced flagellins were not assembled into the flagella filament . The structural and genetic analysis of archaeal flagellin glycosylation is frequently linked with S-layer protein glycosylation, and the reader is referred to a recent detailed review (Jarrell et al, 2010).…”
Section: Archaeamentioning
confidence: 99%
“…-linked glycosylation of proteins is a posttranslational modification found in all three domains of life (12,23,43). While its distribution is apparently rather limited throughout the domain Bacteria, N-linked glycosylation is widespread in the Archaea.…”
mentioning
confidence: 99%